2007
DOI: 10.1029/2006jg000327
|View full text |Cite
|
Sign up to set email alerts
|

Rising minimum daily flows in northern Eurasian rivers: A growing influence of groundwater in the high‐latitude hydrologic cycle

Abstract: A first analysis of new daily discharge data for 111 northern rivers from 1936–1999 and 1958–1989 finds an overall pattern of increasing minimum daily flows (or “low flows”) throughout Russia. These increases are generally more abundant than are increases in mean flow and appear to drive much of the overall rise in mean flow observed here and in previous studies. Minimum flow decreases have also occurred but are less abundant. The minimum flow increases are found in summer as well as winter and in nonpermafros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
197
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(219 citation statements)
references
References 62 publications
(99 reference statements)
15
197
0
2
Order By: Relevance
“…[25] With regard to the dW/dt term in the river basins, other recent studies have indicated that it may be significantly nonzero because of both ongoing permafrost thawing [Adam and Lettenmaier, 2008;Lyon et al, 2009;Lyon and Destouni, 2010] and increasing groundwater flow into rivers in Arctic and subarctic basins [Smith et al, 2007]. New analysis of land water storage from Gravity Recovery and Climate Experiment satellite data also indicates negative dW/dt terms for some major Arctic basins, although data are as yet available only for a few years [Ramillien et al, 2008].…”
Section: Uncertain River Runoff Contribution To Sea Level Changementioning
confidence: 99%
“…[25] With regard to the dW/dt term in the river basins, other recent studies have indicated that it may be significantly nonzero because of both ongoing permafrost thawing [Adam and Lettenmaier, 2008;Lyon et al, 2009;Lyon and Destouni, 2010] and increasing groundwater flow into rivers in Arctic and subarctic basins [Smith et al, 2007]. New analysis of land water storage from Gravity Recovery and Climate Experiment satellite data also indicates negative dW/dt terms for some major Arctic basins, although data are as yet available only for a few years [Ramillien et al, 2008].…”
Section: Uncertain River Runoff Contribution To Sea Level Changementioning
confidence: 99%
“…Other researchers have demonstrated a trend between hydrologic trends and ground thermal regimes in Eurasia. Smith et al [63] noted increasing patterns of minimum daily flows throughout Russia, and these were partly attributed to the reduced influence of seasonal ground freezing. Increased winter flow in the Aldan subbasin of the Lena Basin in Siberia was thought to be related to permafrost thaw [64].…”
Section: The Impacts Of Climate Warming-induced Permafrost Thaw On Wimentioning
confidence: 99%
“…The region also contains the most extensive peatlands on Earth, with peat occurring at up to 5 m depth and holding a substantial fraction of the global terrestrial carbon pool [35,36]. It is also in these permafrost peatlands where the highest lake densities are found [37]. Location of Nadym and Pur river basins, and 7129 sub-basin, thermokarst lake distribution (as of 1973), permafrost distribution, peatland distribution, and areas excluded from the remote sensing study due to cloud cover.…”
Section: Study Areamentioning
confidence: 99%